MENINJAU ULANG KEJADIAN 22:1-19: BENARKAH ALLAH MENGIZINKAN KEKERASAN PADA ANAK? - Siburian, Carel Hot Asi (BONAFIDE: Jurnal Teologi dan Pendidikan Kristen, 2023)
The different images of God in the Old Testament and New Testaments have long been scrutinised. This has resulted in the assertion that the God of the Old Testament favours evil, genocide, murder, etc., whereas the God of the New Testament (in the form of Jesus) is a loving and forgiving God. This article aims to show that God basically does not allow violence against [creation], in this case children, despite the many texts in the Old Testament (one of which is the sacrifice of Isaac) that have this connotation. The findings of this article also vary, ranging from the finding that there is a possibility that the story of Isaac's sacrifice did not happen historically to Abraham's belief that Isaac would still be the son God promised him, so he did not hesitate to sacrifice Isaac. Some [further] findings are also presented in this article, such as the finding of God's tendency to avoid Abraham and Isaac when delivering sacrifices, the possibility that God misused his authority, to the opening of further discussion about how Abraham and Isaac's relationship after they returned home. All of this is presented to show that reading just one text and concluding that God is an evil God is a wrong approach to reading.